2011
DOI: 10.17532/jhsci.2011.98
|View full text |Cite
|
Sign up to set email alerts
|

Effects of improper posture during work on lumbal pain syndrome of discogenic etiology

Abstract: Introduction: Lumbar pain syndrome is the most common cause of why patients, especially the active ones, are reported to physicians. It is manifested as nonspeci¿ c or non-radicular lumbar pain syndrome which is not associated with neurological symptoms, and speci¿ c which is associated with spinal nerve root compression. Aims of this study were to determine correlation between inadequate equipment and improper position for work with disk caused lumbar pain syndrome. Methods: The study included 913 patients wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The study showed that all the examinees took positions which were not optimal while working and it significantly contributed to the MSD occurrence, as Kaljic (1) showed in his paper. The theory that workers (teachers) are the most common patients due to the more frequent mechanic change on their spine is supported by the study (1) done in a policlinic for physical therapy and rehabilitation Stari Grad in the period from April 1st 2004 to December 31st 2009, where they treated 913 patients with pain in the lumbar part of their spine.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The study showed that all the examinees took positions which were not optimal while working and it significantly contributed to the MSD occurrence, as Kaljic (1) showed in his paper. The theory that workers (teachers) are the most common patients due to the more frequent mechanic change on their spine is supported by the study (1) done in a policlinic for physical therapy and rehabilitation Stari Grad in the period from April 1st 2004 to December 31st 2009, where they treated 913 patients with pain in the lumbar part of their spine.…”
Section: Discussionmentioning
confidence: 80%
“…The word "ergonomics" comes from the Greek word ergo, which means "to work", and nomos, which encompasses natural laws or systems (1). Hence, the ergonomics is defined as a science which studies people in relation to their work environment, i.e.…”
Section: Introductionmentioning
confidence: 99%